Iterative decoding and channel estimation of MIMO-OFDM transmissions with hierarchical constellations and implicit pilots - Souto, N. (2007)
In this paper we consider the use of M-QAM hierarchical constellations (Quadrature Amplitude Modulation) combined with implicit pilots for the transmission of multicast and broadcast services in a MIMO-OFDM (Multiple Input Multiple Output - Orthogonal Frequency Division Multiplexing) system. This method of pilot transmission allows coherent detection at the receiver while avoiding the spectral degradation associated with the usual pilot multiplexing techniques but results in mutual interference between pilots and data. Due to the demanding channel estimation requirements and the high sensitivity to interference resulting from the usage of several antennas and hierarchical constellations, an enhanced receiver based on the turbo concept is developed which is capable of dealing with the inherent interference between pilots and data.